BEYOND THE NORM : A CASE SERIES OF MECKELS'S DIVERTICULAM CAUSING INTESTINAL OBSTRUCTION IN THREE DIFFERENT WAYS - Khan, Arif Ullah; Rao Erbaz Hassan,; Khan, Omar; Muhammad Umar Khan Ghauri,; Mashaim Fatima,; M Huzaifa Aurangzeb Mughal,; Abdul Moiz Khan,; Faiza Dawood Khan, (Journal of Ayub Medical College Abbottabad, 2024)
Intestinal obstruction, a critical medical emergency, often attributed to factors like postoperative adhesions, hernias, rarely involves congenital anomalies such as Meckel's diverticulum. Despite its typical asymptomatic nature, Meckel's diverticulum can present challenges, including painless bleeding, and remains an uncommon but perplexing cause of acute intestinal obstruction in adults. This case series describes three unique instances of acute small intestinal obstruction attributed to Meckel's diverticulum, a congenital anomaly that is typically asymptomatic. In contrast to its usual manifestations of painless bleeding or diverticulitis, these cases presented with acute symptoms requiring surgical intervention. The first case involved a young child with a Meckel's diverticulum causing small intestinal obstruction through a narrow based diverticulum with an obstructing stricture. The second case featured a patient with a Meckel's diverticulum causing intestinal obstruction via meso-diverticular band, while the third case involved an eight-year-old with a diverticulum contributing to intussusception. Surgical exploration revealed these uncommon presentations, highlighting the importance of considering rare anatomical variations in the diagnosis and management of intestinal obstruction. This atypical manifestation of Meckel's diverticulum underscores the necessity for timely surgical intervention to address unique presentations not conforming to the usual clinical patterns.